Validación de los indicadores sintomáticos en las estimaciones poblacionales censo del 2000 - Chaves Esquivel, Edwin (2002)
Since the need of having good population estimates to lower administrative areas in the post census periods, it has been proposed the possibility if using auxiliary variables as simple alternative to produce indirect estimates. These variables have been called “Symptomatic indicators” of population change. This article researches about them using information got from the last population and housing census of 2000. It is analyzed the contingence of the produced estimates to cantonal level according to the census value. On the other hand it is discussed the coherence of these results with the ones got in a previous study that was done to census of 1984. The results showed that the combination of the indicators: electoral census, births, primary school registration, can bring right estimates even though there is a strong international immigration. There were used four methods that showed to be a good alternative to get these population estimates.